What is political corruption?: A philosophical analysis - Onah, Gideon Owogeka (Rhodes University, Faculty of Humanities, Department of Philosophy)
The concept of political corruption is crucial in political discourses. Since the 1990s, there has been a massive resurgence of focus on political corruption. Definitional accounts of the concept have been proposed. This work is a critique of the accounts that have since been provided. I argue that these definitions are inadequate, offering an alternative. The predominant definition of the concept is that it refers to public officials' violations of public office rules due to their respective interests in private gain. I consider this wrong for three reasons. First, politics includes more than the activities of public officials. Second, that is not the only behaviour that is contrary to the moral imperatives of politics. Third, the lack of political integrity is not just about acting wrongly. It also includes the possession of political vices. Observing the inadequacy of the dominant perspective, Seumas Miller offers a more comprehensive definition. He defines political corruption as any act that despoils the moral character of political actors and undermines the processes and purposes of legitimate political institutions. However, his definition is also insufficient. First, he includes some immoral non-political acts as examples of political corruption, although he agrees that political corruption entails immorality in politics. Second, he unjustifiably excludes some immoral political actions as denoting political corruption. In contrast, I define political corruption as possessing political vices or acting contrary to moral, political imperatives. This definition is a comprehensive reflection of what it means to lack political integrity. My thesis begins with a critical account of politics and its moral imperatives. That is the criteria for determining what political corruption is.
Keywords: Political corruption; Political ethics; Political science -- Philosophy; Philp, Mark; Thompson, Dennis F (Dennis Frank), 1940-; Miller, Seumas